Modal Sosial Bentukan Dalam Penyelesaian Konflik di Bangka Belitung - Iskandar Zulkarnain; Aimie Sulaiman; Fitri Ramdhani Harahap (Society, 2018)
Three potential conflicts that need to be anticipated in the reality of the life of the Bangka Belitung community in the future. The results of qualitative research through conflict mapping in seven districts / cities showed the potential for economic conflict in fighting for tin resources, agrarian conflicts with development dimensions related to land expansion for large-scale oil palm plantations, and inter-village and interethnic youth conflicts became the dominant issue. The mechanism of the savety valve as a damper of potential recurring conflicts must be institutionalized through functional and sustainable formalized social capital.